Additional file 1 of Integrative analyses of maternal plasma cell-free DNA nucleosome footprint differences reveal chromosomal aneuploidy fetuses gene expression profile - Min Zhang; Kun Li; Shoufang Qu; Zhiwei Guo; Yuanli Wang; Xu Yang; Junhua Zhou; Guojun Ouyang; Rongtao Weng; Fenxia Li; Yingsong Wu; Xuexi Yang (figshare, 2022)
Additional file 1: Table S1. Differential promoter coverage genes and GO, KEGG enrichment analysis results of differential genes for all pregnant women with trisomy.
Keywords: Genetics